Evaluation of Teacher Professional Education Program (PPG) Teaching Graduates in Edge Area, Front Area, and Left Side Area of Indonesia (SM-3T) of Universitas Negeri Padang - Syaiful Haq; M Giatman; Azwar Inra (International Journal of Educational Dynamics, 2019)
The low percentage of 2017 PPT 3T SMT graduates (41.26%) in the National Examination and there are several study programs that did not pass (0%) causing this program to be evaluated. Based on the existing problems, this program must be comprehensively evaluated using the context, input, process & product (CIPP) model. In addition, capability evaluation is an absolute capability that must be possessed by humans in the era of industrial revolution 4.0. This evaluation study ("primary data" quantitatively and qualitative "secondary data") was carried out in the Department of Civil Engineering (Building Tehcnique Education/PTB), Faculty of Engineering, Padang State University (conducting lecturer interviews), online questionnaire (for PPG SM-3T participants), and SMK N 1 and SMK N 5 in Padang City (interviewing teachers involved in the program). The program has been implemented in accordance with its context and has been in accordance with the inputs specified in the program implementation guidelines. but there are problems in the process of implementing the program (79.51%), which has the lowest value. The reason is that the low value of the evaluation process is the different materials tested with those taught during the program, lack of socialization and communication, and discipline. However, product evaluation states that this program has been carried out as evidenced by the results of the categories of both people who have the competencies needed to become professional teachers (pedagogical, professional, personality, and social competencies) according to the program objectives through lecturers and teachers. So it can be concluded that the PPG SM-3T program is worthy of continuing with improvements in the program implementation process.